Penegakan Hukum Terhadap Tindak Pidana Korupsi Proyek Pembangunan Jembatan (Tinjauan Putusan Nomor : 44/Pid.Sus-Tpk/2025/PN.Tjk) - Andriansyah Andriansyah; Sudarmono Sudarmono; Perdana Kusuma; Perdana Putra Saradi (Penerbit Goodwood, 2026)
Purpose: This study examines law enforcement against corruption in bridge construction projects, as reflected in Decision No. 44/Pid. Sus-Tpk/2025/PN.Tjk. This study focuses on analyzing judges’ legal considerations and evaluating the effectiveness of law enforcement in creating deterrent effects and restoring state financial losses caused by corrupt practices in infrastructure development projects. Research Methodology: This study uses a qualitative interpretative approach with a normative juridical method supported by court decision analysis. Data were obtained from legal documents, regulations, and judicial considerations. The analysis applies IFE and EFE matrices, followed by SWOT and QSPM to determine priority strategies. Results: The findings show that anti-corruption law enforcement in bridge construction cases generally ensures legal certainty and procedural justice. However, challenges remain in recovering state losses and preventing systemic corruption. QSPM results indicate that strengthening inter-agency coordination and optimizing compensation penalties are key priority strategies. Conclusions: Effective anti-corruption law enforcement requires stronger institutional coordination, consistent judicial approaches, and optimal implementation of compensation sanctions to strengthen deterrence and accountability in infrastructure projects. Limitations: This study is limited to a single court decision and focuses primarily on normative juridical analysis. Contributions: This study provides strategic recommendations for improving anti-corruption law enforcement and strengthening state financial recovery mechanisms in infrastructure corruption cases in Indonesia.